Professional Development of English Language Teachers in Khandbari Municipality - Guragai, Dandapani (BARUN Journal, 2025)
This article entitled ' Professional Development of English Language Teachers in Khandbari Municipality' is an effort to find the actual situation of professional development of English language teachers in Khandbari Municipality. The article aims to make a link to government's policy to improve the professional development of English teachers and their actual situation in Khandbari municipality and to provide some pedagogical implications. To achieve the objectives different sources of data were applied. It uses quan cum qual research designs. The findings of the study showed that the overall situation of English teachers' professional development is not satisfactory as the teachers of private schools were not involved in the trainings. The major findings of the research are: most of the teachers in community schools are trained and the teachers teaching in this municipality have accepted that the training has enhanced their professional development. The article consists of four chapters followed by references. The first chapter deals with background of the study, statement of the problem, objectives of the study, research questions, significance of the study, delimitation of the study and operational definition of the key terms, review of the theoretical literature and review of empirical literature, and implications of the review of the study. Similarly, the second chapter deals with the research methodology, population and sampling procedure, sources of data, tools of data collection and ethical considerations. The third chapter includes interpretation of results and discussion. Finally, the last chapter consists of conclusion and pedagogical implications.